The Application of Operations Research Information System Tools in Hospital Operations Management in Developing Nations: A Systematic Literature Review - Kagoya, Sumaya M; Mushi, Allen R. (University of Dar es Salaam Library Journal, 2023)
Hospital services in the developing world are always overwhelmed due to scarce resources compared to the demand from the public. Operations Research provides a set of tools that are very useful in the optimization of resources, hence providing a highly needed service in assuring that, the resources are optimally utilized to save lives and provide better healthcare services. This paper reviews applications of Operations Research information system tools(ORIST) in hospital operations to find ORIST status in developing nations like the East African Region.This study used a systematic literature review method and thematic analysis. Results revealed that there is a lot of OR work about hospital operations in the developing world. However, little has been reported from East Africa. A proposal is presented about research opportunities on hospital operations in East African regions by grouping applications into four areas namely; planning, management, medical practice and prevention. The paper concludes by inviting all stakeholders to cooperate and provide the necessary support to Operations-Research practitioners.